OCCURRENCE OF COPPER, CADMIUM, ZINC, AND LEAD IN THE SOILS IN AREAS ADJACENT TO THE BR-010 - Ana Carolina de Castro Cortez; Letícia Eduarda Sousa Vilanova; Rafael de Oliveira Araújo; Jorge Diniz de Oliveira (Revista Eletrônica Científica Ensino Interdisciplinar, 2022)
The concentration of the reference points presented between the government limits is to evaluate the adjacent points. They were produced as combined metals and organic matter, pH in KCl, cation exchange capacity, and bioavailable. Soils have a low content of organic matter and pH at all points indicated as characteristic of medium to organic nature and, in general, inorganic characteristics. The highest CTC observed were in points 3 and 5. As the values of metals must be considered polluting, they show that the control of pollutant emissions is carried out by motor vehicles. Therefore, actions to mitigate environmental damage are important to avoid remote monitoring investigated and avoid serious environmental damage.